Enabling the Circular Economy transition: a sustainable lean manufacturing recipe for Industry 4.0. (7th May 2021) - Ciliberto, Cristina; Szopik‐Depczyńska, Katarzyna; Tarczyńska‐Łuniewska, Małgorzata; Ruggieri, Alessandro; Ioppolo, Giuseppe
Abstract: Over the past 10 years, the concepts and objectives of circular economy have been increasingly detailed and become strategic issues of international, European, and national policies. However, the transition towards circular production models continues to be affected by several barriers and critical factors that make the transition difficult to achieve. The paper tries to design a relationship between sustainable production and lean production, highlighting the opportunity to invest in reverse‐logistics and how Industry 4.0 system represents a breeding ground for circular economy targets application. The aim of the current study is to examine the relationships among sustainable production, lean production, and Industry 4.0 in order to evidence the need to adopt a lean methodology and Industry 4.0 technologies in a sustainable development perspective for companies. Following a holistic vision, the authors summarize the production principles and formulas, which, although in parallel, lead to similar results and therefore represent the pillars of a competitive and sustainable business. In conclusion, exploring the circular economy principles and production chain model, challenges, opportunities, and future outlooks are formulated.